2022
DOI: 10.3389/fimmu.2022.1017863
|View full text |Cite
|
Sign up to set email alerts
|

The third dose of mRNA SARS-CoV-2 vaccines enhances the spike-specific antibody and memory B cell response in myelofibrosis patients

Abstract: Vaccination against SARS-CoV-2 using mRNA-based vaccines has been highly recommended for fragile subjects, including myelofibrosis patients (MF). Available data on the immune responsiveness of MF patients to mRNA SARS-CoV-2 vaccination, and the impact of the therapy with the JAK inhibitor ruxolitinib, are still fragmented. Here, we profile the spike-specific IgG and memory B-cell response in MF patients, treated or not with ruxolitinib, after the second and the third dose of SARS-CoV-2 BNT162b2 (BioNTech) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…In particular, ruxolitinib, a widely used JAKi ( 22 27 ), is known to downregulate immune response with effects on B, T, dendritic, and NK cells ( 28 ) and could be the primary cause of the inferior efficacy of vaccination. Confirming this hypothesis, in patients undergoing ruxolitinib treatment, recently, an impaired response to the first ( 29 ) and second dose of vaccine ( 21 , 47 ) has been demonstrated. Antibodies elicited by vaccination are of key importance to protect subjects from the disease or, in other words, might be able to neutralize the virus ( 38 ).…”
Section: Discussionmentioning
confidence: 71%
“…In particular, ruxolitinib, a widely used JAKi ( 22 27 ), is known to downregulate immune response with effects on B, T, dendritic, and NK cells ( 28 ) and could be the primary cause of the inferior efficacy of vaccination. Confirming this hypothesis, in patients undergoing ruxolitinib treatment, recently, an impaired response to the first ( 29 ) and second dose of vaccine ( 21 , 47 ) has been demonstrated. Antibodies elicited by vaccination are of key importance to protect subjects from the disease or, in other words, might be able to neutralize the virus ( 38 ).…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, booster vaccination may be useful. There have been studies that have explored changes in serum neutralizing antibodies after a third dose of CoronaVac [ 40 , 41 , 42 ] and have shown that neutralization titers (GMT) increased rapidly if a booster was administered 6–8 months after the second dose of CoronaVac, suggesting that a third vaccination could significantly induce an immune recall response in specific memory B cells. Overall, the results of other related studies and our study support the promotion of booster vaccination to reduce the rate of COVID-19 infections, hospitalizations, and mortality [ 17 , 18 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The B cell response has been recently characterized also in fragile patients such as hematopoietic cell transplantation recipients, myelofibrosis patients and people living with HIV, immunized with mRNA vaccines ( 6 , 8 , 33 ). These studies have highlighted the crucial role of the third dose in increasing the frequency of spike-specific B cells, generating a response similar to the one detected in healthy controls.…”
Section: Role Of the B Cell Response Elicited By Vaccinationmentioning
confidence: 99%
“…Confounding factors have been recognized in race, gender, age, comorbidities and immunosuppressive drug treatments (3). For example, age and immunological disorders, which can induce physiological and premature immune senescence, respectively, as well as chronic systemic low-grade inflammation have been considered among the most impacting factors on immune responsiveness to vaccination (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation